DNA fragmentation in hela cancer cell lines treated with syzygium polyanthum extracts - Abdullah, Mastura (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2008)
Plants have a long history of use in the treatment of cancer. Plants have played an important role as a source of effective anti-cancer agents, and it is significant that over 60% of currently used anti-cancer agents are derived from natural sources, including plants, marine organisms and micro-organisms. Methylene blue assay is done to determine the ICso value of Syzygium Polyanthum. IC50 is a concentration that needed to 50% of the cell population death. Plant extract with different concentrations are tested to cells depends on time. After treatment, live cell will take up methylene blue dye and the result will be analyzed by using ELISA reader at 660nm. The effectiveness of the plant extract will be determined based on ICso value. TUNNEL assay is done to detect the rate of apoptosis in HeLa cells treated with S.polyanthum. TUNEL is actually stood for terminal deoxynucleotide transferase dUTP Nick End Labeling. It is use to detect DNA fragmentation that are produced by apoptotic cells. At the last of this experiment, we are able to detect DNA fragmentation event in HeLa cells treated with S.polyanthum extract.